2004
DOI: 10.1016/j.ejpain.2003.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in pain anchors revisited: further investigation of “most intense” and common pain events⋆

Abstract: Recent research suggests that the interpretation of maximal endpoints of pain scales vary between sexes. The purposes of this study were to investigate sex differences in (a) maximal endpoints of pain scales and (b) bias, discrimination, and the "better than average effect" for ratings of common pain events. Study participants described and rated the intensity of events that were the "most intense pain imaginable" for the typical woman, typical man, and one's self. Study participants also described and rated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…The present findings are also in agreement with previous work by our group that demonstrated a high degree of stability of scale anchors 3,18. All these results strongly argue against “scale elasticity” speculations of pain ratings 4.…”
Section: Discussionsupporting
confidence: 94%
“…The present findings are also in agreement with previous work by our group that demonstrated a high degree of stability of scale anchors 3,18. All these results strongly argue against “scale elasticity” speculations of pain ratings 4.…”
Section: Discussionsupporting
confidence: 94%
“…In fact, recent studies highlight the issue of gender difference in pain perception. It has been observed that for the same objective disease women report more pain than men [24]. These observations emphasize the fact that QoL assessment in liver transplant patients should not only include the clinical and biological condition of the patient but also psychosocial and cultural aspects.…”
Section: Discussionmentioning
confidence: 93%
“…Different gender role expectations may lead to different ways in which pain is appraised and dealt with. Evidence suggests that not only do men and women rate men as being less willing to report pain and women more sensitive, but that sex differences in experimental pain reports are at least partially explained by such gender role expectations [67][68][69]. Furthermore, investigations into how observers rate other people's experience of experimentally induced pain reveal that (a) female observers rate pain intensity in both men and women as being higher than male observers and (b) observer expectations of gender-related pain is related to their subsequent pain ratings of others [70].…”
Section: Social Influencesmentioning
confidence: 97%